2020
DOI: 10.1021/acs.jmedchem.0c00814
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel pERK1/2- or β-Arrestin-Preferring 5-HT1A Receptor-Biased Agonists: Diversified Therapeutic-like versus Side Effect Profile

Abstract: Novel 1-(1-benzoylpiperidin-4-yl)methanamine derivatives with high affinity and selectivity for serotonin 5-HT 1A receptors were obtained and tested in four functional assays: ERK1/2 phosphorylation, adenylyl cyclase inhibition, calcium mobilization, and β-arrestin recruitment. Compounds 44 and 56 (2-methylaminophenoxyethyl and 2-(1 H -indol-4-yloxy)ethyl derivatives, respectively) were selected as biased agonists with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…A recent study by Sniecikowska et al ( 2020 ) has identified new 5-HT 1A -specific antidepressant compounds, highlighting the importance of endosomal signaling through 5-HT receptors in regards to developing novel antidepressants. “Compound 44” induced potent ERK activation, while inducing β-arrestin recruitment to 5-HT 1A and cAMP production at a level comparable to serotonin.…”
Section: Serotonin Receptor and Transporter Endocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Sniecikowska et al ( 2020 ) has identified new 5-HT 1A -specific antidepressant compounds, highlighting the importance of endosomal signaling through 5-HT receptors in regards to developing novel antidepressants. “Compound 44” induced potent ERK activation, while inducing β-arrestin recruitment to 5-HT 1A and cAMP production at a level comparable to serotonin.…”
Section: Serotonin Receptor and Transporter Endocytosismentioning
confidence: 99%
“…“Compound 56” potently induced β-arrestin recruitment compared to serotonin or compound 44, and increased ERK activation and cAMP production to a much greater extent than compound 44. Compound 56 also acted as an antidepressant in mice, but also led to serotonin syndrome (i.e., serotonin overdose) (Sniecikowska et al, 2020 ). Similar to cAMP, ERK can be activated at the plasma membrane or intracellular compartments by either G-proteins or β-arrestins (Eishingdrelo, 2013 ).…”
Section: Serotonin Receptor and Transporter Endocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…This type of assay was originally applied to discover biased ligands that favor G-protein signaling for opioid receptors [61], ultimately resulting in the first drug designed as a biased agonist, oliceridine (FDA-approved in August 2020), which has reduced adverse effects compared with morphine. Similar assays have facilitated the discovery of biased ligands for the nociception opioid peptide (NOP) [62] and serotonin HT1A [63] receptors. Although ion channel/transporter interactions with function-modulating proteins are not as well characterized compared with GPCRs, there is great potential to apply similar assays to those systems, as in a recent example where a peptide disrupting the Na v 1.6/fibroblast growth factor interaction was discovered [64].…”
Section: Hts Approachesmentioning
confidence: 99%
“…As for many GPCRs, biased ligands acting on 5-HT receptors are actively searched in order to obtain more selective drugs with fewer side effects 62 65 . Agonists acting at 5-HT 2A receptors represent one of the most striking illustrations of functional selectivity 66 , 67 .…”
Section: Biased Agonism At 5-ht 2a Receptor: Impact Of Its Heteromerization With Mglu 2 Receptormentioning
confidence: 99%